Enhancing Nurse Well-Being: The Role of Self-Compassion in Flourishing - Kurniawan, Baby Ayline; Kusumiati, Ratriana Yuliastuti Endang (Jurnal Bimbingan dan Konseling Terapan, 2024)
This study explores the relationship between self-compassion and flourishing among nursing staff at RSUD Salatiga. Utilizing a quantitative correlational design, data were collected from 131 nurses through purposive sampling and analyzed using Pearson's Product Moment Correlation. The self-compassion and flourishing variables were measured using the Self Compassion Scale Short Form (SCS-SF) and PERMA profiler, respectively. Results indicated a significant positive correlation (r = 0.266, p = 0.002), with self-compassion contributing 7.1% to the variance in flourishing. Descriptive statistics revealed that 33.6% of participants had high self-compassion, and 62.6% had very high flourishing. Most participants were women (80.2%) and adults aged 20-40 years (56.5%), groups typically associated with higher flourishing levels. The findings underscore the importance of self-compassion in enhancing nurses' well-being, supporting previous research on its role in emotional regulation, stress reduction, and overall mental health. Despite administrative challenges, this study offers valuable insights into promoting self-compassion to improve the quality of patient care in healthcare settings.